“En torno al Neptuno alegórico de sor Juana” - Alatorre, Antonio (El Colegio de México, 2010)
Critique of Catedra’s edition of Neptuno alegórico. Electa Arenal’s introductionabounds in exaggerations and inaccuracies. On the other hand, thetext, in charge of Vincent Martin, is commendable, except for a few details.In her work, sor Juana quotes sixty ancient authors, which gave her the reputationof being very knowlegeable; in fact, all her erudition depends onthree or four reference books, especially Baltasar de Vitoria’s Teatro de losdioses de la gentilidad. Martin’s explanations are rather pertinent, althoughsometimes problematic: in some instances, he alters sor Juana’s text withoutapparent reason, he is guilty of a few errata, and adds comments that sometimescall for rectificacion. Anyway, thanks to him, the terrain is ready fora future impeccable edition.